2012
DOI: 10.1021/ie300416n
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Supported Fenton-Like Systems for the Catalytic Wet Peroxide Oxidation of Phenol Solutions

Abstract: Fe2O3/Al2O3 catalysts (2% Fe) were prepared and characterized by XRD, BET, Raman, and SEM-EDAX. The systems were tested for the catalytic oxidation of phenol solutions (5000 ppm) with H2O2. The effects of reaction temperature, catalyst loading, phenol initial concentration, and H2O2:phenol molar ratio were evaluated. The relatively low oxidant consumption rates favored increased mineralization levels at substoichiometric H2O2 initial concentrations. The stability of the catalytic system was improved by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Active phase remained almost constant through all the distance, indicating a uniform distribution of copper species [30]. This diffusion of active species to inner zones of the support is probably a consequence of the high calcination temperature [31]. According to Fig.…”
Section: Catalyst Characterizationmentioning
confidence: 78%
“…Active phase remained almost constant through all the distance, indicating a uniform distribution of copper species [30]. This diffusion of active species to inner zones of the support is probably a consequence of the high calcination temperature [31]. According to Fig.…”
Section: Catalyst Characterizationmentioning
confidence: 78%
“…A higher amount of Fe(II) diminish the reaction delay. It has been reported that quinone and quinone-like compounds such as hydroquinone or catechol function as reducing agents for Fe(III), promoting the Fenton reaction [70][71][72][73]. Therefore, the fast occurrence of these intermediates at 70 • C could also reduce the induction period.…”
Section: 222mentioning
confidence: 99%
“…[17] This unique quality of alumina encouraged the researchers to engage iron oxide supported alumina catalysts for the degradation of phenol up to 5000 ppm. [18][19][20][21][22][23][24][25][26][27][28][29][30] Notably, Bautista et al studied the performance of Fe 2 O 3 /Al 2 O 3 powdered catalyst (4%Fe) in the CWPO of phenol up to 1500 ppm. However, the leached iron content in the water increased up to 10% with an increase in the initial phenol concentration, and a decrease in the mineralization levels (42%) was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Similarly, Fenoglio et al experimented iron oxide supported alumina as heterogeneous Fenton catalyst for the degradation of high concentration of phenol up to 5000 ppm. [24,28] It was observed that under a constant iron loading (4 wt%) the increased alumina support favors the iron oxide dispersion which led to the high degradation of phenol due to the synergistic effect of Fe/Al interactions with improved leaching stability of the catalyst. Nevertheless, the achieved iron oxide in a highly dispersed state not only limits the iron oxide loading but also demands a high amount of alumina support.…”
Section: Introductionmentioning
confidence: 99%